2009
DOI: 10.1111/j.1365-246x.2009.04231.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring remanence anisotropy of hematite in red beds: anisotropy of high-field isothermal remanence magnetization (hf-AIR)

Abstract: S U M M A R YThe potential of using high-field anisotropy of isothermal remanence magnetization (hf-AIR) measurements for determining the origin of natural remanent magnetization in red beds and for identifying and correcting possible red-bed inclination shallowing was investigated for specimens of the Carboniferous Shepody Formation of New Brunswick and Nova Scotia, Canada. The technique makes it possible for a typical paleomagnetic laboratory to measure the remanence anisotropy of high-coercivity hematite.Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…This bias is known as the shallow bias of inclination angle in sedimentary rocks. [ Jackson et al ., , Tan et al ., , Bilardello and Kodama , , and Kodama , ]. We applied the method proposed by Tan and Kodama [] using anisotropy of anhysteretic remanent magnetization data for the correction of the inclination shallowing.…”
Section: Discussionmentioning
confidence: 99%
“…This bias is known as the shallow bias of inclination angle in sedimentary rocks. [ Jackson et al ., , Tan et al ., , Bilardello and Kodama , , and Kodama , ]. We applied the method proposed by Tan and Kodama [] using anisotropy of anhysteretic remanent magnetization data for the correction of the inclination shallowing.…”
Section: Discussionmentioning
confidence: 99%
“…1b), and combined datasets yield an inclination that would suggest a paleolatitude of 11.2 • N [7.7 • N, 14.9 • N]. We cannot apply neither the E/I method (Tauxe and Kent, 2004), nor the anisotropy-based correction method (Tan et al, 2003;Bilardello and Kodama, 2009) to assess the magnitude of inclination shallowing in these rocks due to the limited number of isolated ChRM directions and the unavailability of magnetic fabric data. The strongly elongated distribution of the VGPs (Fig.…”
Section: Where Did the Xigaze Ophiolite Form?mentioning
confidence: 92%
“…Individual magnetic particle anisotropy can be measured directly using specialized laboratory equipment (e.g., Kodama, 1997); it can also be determined by least-squares curve fitting of AMS, AARM (for magnetite) and AIR (for hematite) data (Tan et al, 2003;Bilardello and Kodama, 2009;Kodama, 2009). Our rock magnetic analyses and results of end-member modeling have indicated that magnetite is the dominant magnetic carrier in the Sangsang section.…”
Section: Anisotropy-based Inclination Correctionmentioning
confidence: 99%
“…Under these circumstances, one would ideally isolate the anisotropy due to hemo‐ilmenite and compare the direction and intensity of the NRM to that component of the anisotropy. However, isolating the anisotropy of a high‐coercivity low‐magnetization mineral that coexists with magnetite is difficult, as has been shown for hematite [ Bilardello and Kodama , ; Kodama and Dekkers , ]. Biedermann et al .…”
Section: Discussionmentioning
confidence: 99%